Squeezed fermions and back-to-back correlations - Panda, P. K.; Csorgo, T.; Hama, Y.; Padula, S. S. (World Scientific Publ Co Pte Ltd, 2001)
Back-to-back correlations of asymptotic fermion-anti-fermion pairs appear if in-medium interactions lead to mass modifications of fermion states in a thermalized medium. The back-to-back correlations of protons and anti-protons will be experimentally observable in ultrarelativistic heavy ion collisions. The strength of back-to-back correlations of fermions can be unlimitedly large, diverging as the momentum of the pair increases and the net baryon density decreases.